2005
DOI: 10.1210/jc.2005-0086
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Markers of Bone Turnover in Boys with Constitutional Delay of Growth and Puberty

Abstract: It has been suggested that poor growth in childhood or puberty might be a correctable determinant of osteoporosis. To assess the effect of the growth and puberty delay on bone metabolism, we measured bone mineral density (BMD) and markers of bone turnover in 41 boys with constitutional delay of growth and puberty. Total body (TB) and lumbar spine (LS) BMD were measured by dual-energy x-ray absorptiometry. Serum osteocalcin, total alkaline phosphatase, and urinary deoxypyridinoline cross-links as markers of bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…(8)(9)(10) A study including boys (8-18 years of age) with constitutional delay of growth and puberty found that BMD, measured with dualenergy X-ray absorptiometry (DXA), adjusted for bone age increased throughout pubertal stages in a similar manner as in healthy children. (11) Less is known about how adult BMD in men is affected by variations in pubertal timing within the normal range. We have earlier reported, in the Gothenburg Osteoporosis and Obesity (GOOD) study of 19-year-old males in Sweden, that late but normal puberty was associated with lower BMD and previous fracture in a cross-sectional study.…”
Section: Introductionmentioning
confidence: 99%
“…(8)(9)(10) A study including boys (8-18 years of age) with constitutional delay of growth and puberty found that BMD, measured with dualenergy X-ray absorptiometry (DXA), adjusted for bone age increased throughout pubertal stages in a similar manner as in healthy children. (11) Less is known about how adult BMD in men is affected by variations in pubertal timing within the normal range. We have earlier reported, in the Gothenburg Osteoporosis and Obesity (GOOD) study of 19-year-old males in Sweden, that late but normal puberty was associated with lower BMD and previous fracture in a cross-sectional study.…”
Section: Introductionmentioning
confidence: 99%
“…Bone-type alkaline phosphatase is often used as a representative bone metabolism marker related to bone formation (Frost et al 2004;Iba et al 2004;de Papp et al 2007). Deoxypyridinoline (DPD) is often used as a bone metabolism marker related to bone resorption (Kitatani et al 2003;Krupa and Miazgowski 2005;Millet et al 2005). Bone metabolism markers are measured in blood or urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in a pediatric study, BMD and bone turnover markers (serum osteocalcin, total alkaline phosphatase, and urinary D-pyd) were evaluated in 41 boys with CDGP between stages I-IV of puberty and authors reported that in boys with CDGP, like normal boys, BMD adjusted for bone age increases parallel to the stages of puberty, and the most significant BMD increments took place between stages III and IV. They recommended that in boys with CDGP, bone turnover was similar with that of healthy children (7). In a study from Italy, 21 adult men with CDGP and 12 healthy men as a control group were compared.…”
Section: Discussionmentioning
confidence: 99%
“…This is suggested as a risk factor for development of osteopenia and bone fractures (1)(2)(3)(4)(5). Contrarily, some authors indicated that bone remodeling-related biochemical parameters of cases with CDGP are not different than normal values, therefore, their bone mineral density (BMD) and fracture risks remain unchanged (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%